2018
DOI: 10.3389/fphar.2018.00866
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Promotes Chemoresistance Through the Reduction of the Mitochondrial DNA Damage, the Bax/Bcl-2 and Bax/Bcl-XL Ratio, and the Cells in Sub-G1 Phase Due to Antitumoral Drugs Induced-Cytotoxicity in Human Colon Adenocarcinoma Cells

Abstract: Diabetes and cancer are common, chronic, and potentially fatal diseases that frequently co-exist. Observational studies clearly indicate that the risk of several types of cancer is increased in diabetic patients and a number of cancer types have shown a higher mortality rate in patients with hyperglycemic associated pathologies. This scenario could be due, at least in part, to a lower efficacy of the cancer treatments which needs to be better investigated. Here, we evaluated the effects of a prolonged exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Gu et al (34) showed that BC200 can affect the expression of Bax and Bcl-2, suggesting that BC200 is involved in the apoptosis of colorectal cancer (CRC) cells. It has been previously reported that the ratio of Bax/Bcl-xL can be used to measure the level of apoptosis (35). In the present study, following BC200 KO, Bax protein expression was decreased and Bcl-xL protein expression was increased.…”
Section: Discussionsupporting
confidence: 54%
“…Gu et al (34) showed that BC200 can affect the expression of Bax and Bcl-2, suggesting that BC200 is involved in the apoptosis of colorectal cancer (CRC) cells. It has been previously reported that the ratio of Bax/Bcl-xL can be used to measure the level of apoptosis (35). In the present study, following BC200 KO, Bax protein expression was decreased and Bcl-xL protein expression was increased.…”
Section: Discussionsupporting
confidence: 54%
“…One of the major challenges is the poor response to the chemotherapeutic drugs. Recent studies have shown that high blood sugar levels can lead to oxaliplatin resistance in patients with Stage III colorectal cancer [33,34]. Similarly, in breast cancer, hyperglycemia induced resistance was observed in the ER+ types [35].…”
Section: Discussionmentioning
confidence: 99%
“…A number of medical conditions can increase blood glucose concentration (hyperglycemia), including diabetes mellitus (DM), obesity, pancreatitis, chronic stress, and cancer [35, 36], and hyperglycemia has been shown to attenuate tumor therapeutic response and to confer resistance to chemotherapy-induced cell death [37, 38]. At molecular level, HG modulates various signaling pathways that control cancer cell proliferation, migration and recurrence [39, 40], as well as apoptosis [27, 3943]. In our previous studies we showed that HG reduces ADR-induced cell death.…”
Section: Discussionmentioning
confidence: 99%